Inter-individual Variability in Psychological Outcomes of Supervised Exercise in Adults with Type 2 Diabetes / Variabilidad interindividual en los efectos psicológicos del ejercicio supervisado en adultos con diabetes tipo 2 - Marco Guicciardi; Romina Lecis; Davide Massidda; Lucina Corgiolu; Adelina Porru; Matteo Pusceddu; Francesca Spanu (Revista Costarricense de Psicología)
Abstract: